2013
DOI: 10.1136/bjophthalmol-2012-302199
|View full text |Cite
|
Sign up to set email alerts
|

Interferon γ release assay for the diagnosis of uveitis associated with tuberculosis: a Bayesian evaluation in the absence of a gold standard

Abstract: The T-SPOT.TB assay is more specific but less sensitive than the TST and should be used in preference to the TST in low-TB-prevalence populations. Used in conjunction, the likelihood of TAU is greatest if the T-SPOT.TB and TST are both positive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 26 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…Gineys et al 9 reported 44% QFT-G positivity in presumed ocular tuberculosis in a low TB endemic country while Ang et al 10 reported 66% QFT-G positivity in presumed ocular tuberculosis in a moderate TB endemic country. Gineys et al reported encouraging results with ATT in patients with values over 2 IU.…”
Section: --mentioning
confidence: 97%
“…Gineys et al 9 reported 44% QFT-G positivity in presumed ocular tuberculosis in a low TB endemic country while Ang et al 10 reported 66% QFT-G positivity in presumed ocular tuberculosis in a moderate TB endemic country. Gineys et al reported encouraging results with ATT in patients with values over 2 IU.…”
Section: --mentioning
confidence: 97%
“…Current evidence shows that while TST is more sensitive [ 278 ], QFT and T-SPOT are more specifi c for the diagnosis of presumed ocular tuberculosis ( [ 11 , 12 ], EBM: C, 2+). TST and T-SPOT test should be the investigation of choice in high and low endemic populations, respectively ( [ 12 ], EBM:C, 2+).…”
Section: Diagnosismentioning
confidence: 99%
“…However, the diagnosis of tuberculous uveitis is challenging due to low yield from cultures of intraocular samples given the small sample volumes and low bacterial load 2. As such, tuberculous uveitis is currently diagnosed using a combination of suggestive clinical features (broad-based posterior synechiae, granulomatous inflammation, serpiginious choroiditis, retinal vasculitis) in combination with concomitant evidence of active or latent systemic tuberculosis (TB) 3.…”
Section: Introductionmentioning
confidence: 99%